Betas versus characteristics: A practical perspective. (14th May 2020) - Nazaire, Gregory; Pacurar, Maria; Sy, Oumar
Abstract: We apply a new dummy‐variable method to examine which factor exposures (betas) and characteristics provide independent information for US stock returns in the context of the multifactor models of Hou, Xue, and Zhang and of Fama and French. We find that betas related to market, size, value, momentum, investment, and profitability factors are not priced. In contrast, firm characteristics related to size, value, investment, and profitability have significant and independent explanatory power, suggesting that they are important in determining expected returns. Finally, the cross‐sectional effect of momentum is subsumed when the return on equity is factored in.